1987
DOI: 10.1002/pen.760270904
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties and permeability of polypropylene and poly(ethylene terephthalate) mixtures

Abstract: The synthetic membranes currently used for soil stabilization and road construction are mainly made of polypropylene and of polyesters. They are used separately for each application. The polymer used has an effect on the wettability and, the permeability of the membrane. The polypropylene membranes, for instance, have a zero wettability, whereas it is high for polyester membranes. This paper reports on the mechanical properties and the permeability of mixtures of polypropylene (PP) and poly(ethylene terephthal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
38
0
6

Year Published

1997
1997
2007
2007

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 79 publications
(46 citation statements)
references
References 5 publications
2
38
0
6
Order By: Relevance
“…Marked negative deviations from simple additivity are observed from the figures for both the ultimate strength and the elongation at break over the entire composition range, which is typical for an essentially incompatible system. [20][21][22][23][24][25] It may be reasonable to conclude that interfaces between ETFE and PVF 2 are weakly bonded with rather poor interaction. .…”
Section: Tensile Propertiesmentioning
confidence: 99%
“…Marked negative deviations from simple additivity are observed from the figures for both the ultimate strength and the elongation at break over the entire composition range, which is typical for an essentially incompatible system. [20][21][22][23][24][25] It may be reasonable to conclude that interfaces between ETFE and PVF 2 are weakly bonded with rather poor interaction. .…”
Section: Tensile Propertiesmentioning
confidence: 99%
“…1 Blends of PET with polyolefins are known to improve certain properties of the PET when an interfacial modifier is added to the blend. [2][3][4][5][6][7][8][9][10][11] Barlow et al 2 and Chen et al 3,4 showed that styrene-ethylene-butylenestyrene (SEBS) results in an increase of the ductility of such a blend. Nevertheless, more pro-nounced effects are observed when a functionalized copolymer is used and, more precisely, a grafted maleic anhydride SEBS copolymer.…”
Section: Introductionmentioning
confidence: 99%
“…This forms an in situ generated SEBS-g-PET during melt blending. It is well know in the literature that primary alcohols with a hydrocarbon chain longer than C 5 have a tendency to react with cyclic anhydride functions. 13 The esterification is an exothermic reaction that follows second order kinetics.…”
Section: Introductionmentioning
confidence: 99%
“…Without any specific interactions, PP is unlikely to form miscible blends or even to adhere to other polymers (3). There are several examples of PP blended with polyesters (4,5). Typically when PP is blended with the liquid crystalline polyester (LCP), the mechanical strength is improved due to fiberlike LCP phases in the flow direction.…”
mentioning
confidence: 99%
“…By addition of some maleic anhydride modified PP in the melt blending of PP and LCP, impact and tensile strength of blends significantly improved (4). Blends of PP and poly-(ethylene terephthalate) (PET) have likewise been improved by the addition of acrylic acid modified PP (5). Therefore, the presence of chemical functionalities such as carbonyl and hydroxyl groups would be usefull to increase interaction such components in a polyblend.…”
mentioning
confidence: 99%